Calibration Of Vickers Hardness Test PT.Tenaris Seamless Pipe Indonesia Jaya Cilegon Using Standar Blok - Dodi Sofyan Arief; Muftil Badri; M. Dalil; Agus Reforiandi; Agus Surya Permana (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
A calibration is an activity to determine the conventional validity of the appointment value of measuring instruments and measuring materials by comparing them to standard measurements that are traceable to national and international standards for measurement units and or international and certified reference materials. The calibration is generally a process of adjusting the output or indication of a measurement device to match the magnitude of the standard used in certain accuracy. The purpose of this paper is to find out the vickers hardness test calibration whether the machine running normally or there is a problem with the device. A case study was conducted in PT. Tenaris SPIJ, Cilegon, Indonesia. A vickers hardness testing in the case study has its own reference standard, namely ISO 6507-2: 2018 Metal material - Hardness Test Verification and Calibration of the test machine. The vickers hardness test equipment is a machine to conduct tests using a diamond pyramid with a plane angle of 136°, by means of an emphasis by an indentor that results in a trace or indentation on the surface of the test object. The vickers hardness testing is abbreviated as HV or HVN and also known as Diamond Pyramid Hardness Test (DPH). Result of calibration in the case study was found the repeatability value on vickers hardness testing machine of 32 HV 10 and the error value of ±3%.